2018
DOI: 10.1002/mcf2.10022
|View full text |Cite
|
Sign up to set email alerts
|

A spatiotemporal Evaluation of Atlantic Sea Scallop Placopecten magellanicus Habitat in the Gulf of Maine Using a Bioclimate Envelope Model

Abstract: A bioclimate envelope model was developed to evaluate the impacts of climate variability on spatiotemporal availability of suitable habitat for the Atlantic sea scallop Placopecten magellanicus in the Gulf of Maine (GOM). Bioclimate envelopes were established through habitat suitability indices (HSIs) based on bottom temperature, bottom salinity, current velocity, depth, and bottom composition. The relationship between Atlantic sea scallop abundance and each environmental variable was quantified using suitabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 51 publications
2
4
0
1
Order By: Relevance
“…The TPRS GAM, incorporating a Tweedie distribution for zero-inflated catch data was shown to be a useful prediction tool according to cross validation. The response curves in general agreed with known information about drivers of scallop distribution (Naidu and Anderson, 1984;Thouzeau et al, 1991;Wildish and Kristmason, 1993;Stewart and Arnold, 1994;Pilditch and Grant, 1999;Hart and Chute, 2004;Torre et al, 2018).…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…The TPRS GAM, incorporating a Tweedie distribution for zero-inflated catch data was shown to be a useful prediction tool according to cross validation. The response curves in general agreed with known information about drivers of scallop distribution (Naidu and Anderson, 1984;Thouzeau et al, 1991;Wildish and Kristmason, 1993;Stewart and Arnold, 1994;Pilditch and Grant, 1999;Hart and Chute, 2004;Torre et al, 2018).…”
Section: Discussionsupporting
confidence: 75%
“…A dominant spatial trend made apparent by this climate-niche SDM is a decline in predicted density moving from inshore to offshore locations. This finding corresponds with habitat value for scallops being higher among inshore areas relative to offshore areas likely attributed to deteriorating food availability moving offshore (Torre et al, 2018). This is thought to represent a natural gradient of habitat quality (Sarro and Stokesbury, 2009).…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Fisheries resources and habitats are subject to natural and anthropogenic stressors (Saba et al, 2015), including warming temperatures from climate change (Henson et al, 2017), ocean acidification (Kroeker et al, 2013), and ocean deoxygenation (Oschlies et al, 2018). Rapid climate-induced shifts are affecting habitats and species distributions in proposed wind development areas (Torre et al, 2018). Nye et al (2009) evaluated changes in the distributions of 36 fish stocks in northeast US continental shelf waters between 1968 and 2007 and showed that the biomass of many of these stocks shifted toward the north and expanded into deeper habitats and cooler waters in response to climate-driven environmental changes.…”
Section: Offshore Wind Will Create Changementioning
confidence: 99%